Calcific Tendinopathy of the Shoulder - Bureau, Nathalie J. (Seminars in Musculoskeletal Radiology, 2013)
This review article presents the current knowledge on the epidemiology and the pathogenesis of calcific tendinopathy of the shoulder and discusses the clinical presentation in relation to the stage of the disease process and the appearance of the calcific deposits. The outcome and the available treatment modalities for this common shoulder disorder are also examined, emphasizing the technique of percutaneous lavage and aspiration under ultrasound guidance.
Keywords: calcific tendinopathy; shoulder; ultrasound; lavage